SEJARAH GERAKAN DAKWAH ABDUL GHANI KASUBA (JIHAD PERDAMAIAN PADA KONFLIK ANTAR AGAMA DI MALUKU UTARA) - Abdullah, Siti Nuralfia (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2020)
The way of Islamic preaching from the time of the Prophet to the present can be said to be diverse. In its development, some famous figures, scholars, and religious teachers also emerged in their respective regions. Each figure also has a different path and experience in the preaching of all fields, including the daâ€™wa jihad carried out by Abdul Gani Kasuba in breaking up inter-religious conflicts in North Maluku. This article uses the method of library research in which is data is taken from the main resources, namely â€œSejarah Konflik dan Perdamaian di Maluku UtaraÂ (Refleksi Terhadap Sejarah Moloku Kie Raha)â€ and â€œKonflik Komunal: Maluku 1999-2000â€. As a result, the author concludes that the substance of the missionary movement of Abdul Gani Kasuba is showing a humanist person to the community when preaching, regardless of which people he preaches. He prioritizes the characteristics of ukhuwah wathaniyah that implies the importance of brotherhood based on humanity (ukhuwah basyariah).Â Â .